Mãe Africana, Pátria Brasileira: negotiating the racial politics of identity, freedom and motherhood in nineteenth-century Bahia, Brazil - Collins, Jane-Marie (Liverpool University Press, 2013)
Margarida Ignácio de Medeiros was one of up to twelve million enslaved Africans brought to Brazil. She did not, however, remain enslaved all her life. Margarida’s trajectory from enslavement to freedom was typical of many enslaved African women labouring in urban centres of nineteenth-century Brazil. Although regarded as a domestic slave her enslaved working life, and day, was divided between house and street. Margarida’s work in the house provided her owner with domestic comfort, while her work in the street provided her with an income. Allowed to retain a portion of that income, Margarida was eventually able to purchase her freedom. While living with her owner, Margarida also (re)produced free born children over whom her owner tried to obtain custody.